Study on the degradation and metabolic mechanism of four quinolone antibiotics by mixed strains - Wang, Hongdan; Wang, Qiaoning; Lv, Min; Song, Zhihua; Yu, Jialuo; Wang, Xiaoyan; Li, Jinhua; Chen, Lingxin (Frontiers in Environmental Chemistry, 2024)
Quinolone antibiotics are a common class of antibiotics in the environment and and have received considerable attention. In this study, three groups of mixed degradation strains targeting mixed quinolone antibiotics, norfloxacin (NOR), and enrofloxacin (ENR) were selected through screening, enrichment, and microbial diversity detection experiments. The strains screened in this study are divided into two categories through degradation efficiency experiments, community composition detection and functional enrichment analysis. In groups mix and ENR, the resistant bacteria are the main microorganisms and the degrading bacteria are the secondary ones, while in group NOR, the strains with degradation effects are the main ones, and the strains with resistance effects are the secondary ones. What's more, that carbon sources have little effect on the community composition of the quinolone antibiotic degrading and tolerant bacteria, the difference between groups is mainly controlled by the type of antibiotics.On this basis, we found the key to NOR degradation is the cleavage of carbon nitrogen bonds on the piperazine ring, followed by oxygenation and deethylation. Preliminary studies have confirmed that the optimal degradation conditions for NOR degrading strains, and also found that environmental factors did not significantly affect the degradation efficiency of the Mix and NOR degrading strains, which indicating that the mixed bacteria can degrade NOR in different real environments effectively such as tap water, seawater, river water, and lake water. This manuscript is the first report on a mixed strain of quinolone antibiotic microbial degradation, and it is also the study with the highest NOR degradation efficiency among known reports. It has great research value for the co-metabolism and biodegradation of quinolone antibiotics in the environment.